(untitled) (Revista Brasileira Multidisciplinar, 2013)
Obesity is a multifactor chronic disease and its incidence has been increasing over the years and is being considered a public health problem. It is characterized by a chronic state of low grade inflammation, in which the C-reactive protein levels are usually increased. This inflammatory process can change the endothelial function in these individuals, since elevated levels of C-reactive protein are related to a low production of nitric oxide, which is responsible for the endothelium vasodilation. Several studies have demonstrated the influence of polymorphisms in the genes of C-reactive protein and of the endothelial nitric oxide synthesis enzyme in obese and healthy individuals. Thus this literature review aims at discussing the relationship between obesity and C-reactive protein levels and endothelial function, as well as to elucidate the association of genetic factors. Scientific articles from the databases PubMed, Science Direct and Scielo were consulted, using the following keywords and combinations of them: C-reactive protein, function/endothelial dysfunction, polymorphism and obesity. Thus, we concluded that obese individuals have elevated levels of C-reactive protein as a result of excess of body fat and this implies a reduction in nitric oxide synthesis. All these factors can be influenced by polymorphisms in regulatory genes of the production of these proteins.